A Socio-pragmatic Analysis of Threatening UtterancesIn Action Films and Their Subtitles - Dewi, Dian Ayu Rosita (2011)
This research deals with threatening utterances in action films and their subtitles. The aims of this research are to identify the variation of language form of threatening utterance in action films and their Indonesian version, to describe the equivalence of intention of threatening utterance in action films and their subtitles, and to describe the equivalence of politeness strategy of threatening utterance in action films and their subtitles. The researcher employs the descriptive qualitative as a type of the research. The data source of this research is action films and their subtitles. The methods of collecting data are documentation and observation. The techniques of analyzing data of this research are describing the form by referring to linguistic form, analyzing the intention based on speech act theory and describing the politeness pattern by referring politeness strategy. This research shows the variation of the sentence types, the equivalence of intentions and the equivalence of politeness pattern of threatening utterances in action films and their subtitles. The variations of type of sentences are: declarative, imperative, and interrogative. While the sentences form variations are: simple sentence is subtitled into simple sentence, compound sentence is subtitled into complex sentence is subtitled into complex sentence, and complex-compound sentence is subtitled into complex sentence. The intentions of the threatening utterance are: threatening, asserting, showing power/ability, warning, commanding, and encouraging. The politeness pattern is divided into three kinds, they are: Bald on record, Positive Politeness, Negative Politeness, and Off Record Strategy.